Molecular‐sieve‐based matrix solid‐phase extraction combined with field‐amplified sample stacking in capillary electrophoresis for the determination of three organic acids in a complex solid matrix. Issue 19 (14th August 2018) - Wei, Mengmeng; Liu, Caijing; Zhang, Huan; Jiang, Luyi; Yan, Jizhong; Chu, Chu
Abstract: A simple, convenient, and sensitive method that involves combining matrix solid‐phase dispersion extraction with field‐amplified sample stacking in capillary electrophoresis has been developed for the determination of organic acids in a complex solid matrix. Mesoporous molecular sieve, MCM‐48, was synthesized by a hydrothermal method and selected as the adsorbent in matrix solid‐phase dispersion. After fast extraction, the enriched analytes were back‐extracted into a basic aqueous solution for field‐amplified sample stacking in capillary electrophoresis. Parameters that affect extraction efficiency and sample stacking were optimized. Under the optimal conditions, approximately 42‐, 49‐, and 56‐fold sensitivity enhancements were achieved for danshensu, protocatechuic acid, and cinnamic acid, respectively, when compared to normal injection. A satisfactory correlation coefficient ( r > 0.99) was obtained. Both intra‐ and interday precision were lower than 2.53%. And the limits of detection of the three organic acids ranged between 0.01 and 0.029 μg/mL. Finally, the newly proposed method was successfully applied to the determination of organic acids in Fufang Danshen tablets, which indicates its great potential in analyzing organic acids in a complex matrix.